Avian mycoplasmosis monitoring in the Russian Federation in 2019 - A. E. Menshchikova; T. N. Brundakova; M. S. Volkov; V. N. Irza (Ветеринария сегодня, 2020)
Under the conditions of intensive poultry farming and high concentration of poultry in a limited area mycoplasmoses cause significant economic damage to commercial poultry farming. Of greatest interest are respiratory mycoplasmosis and infectious synovitis, the causative agents of which are Mycoplasma gallisepticum and Mycoplasma synoviae, respectively. Considering that both diseases are included in the OIE list of notifiable diseases, it is necessary to perform constant control for their spread. The paper presents an analysis of serological test results for antibodies to mycoplasmosis agents in 2019. Six respiratory mycoplasmosis positive samples – and 129 infectious synovitis positive samples were detected when testing 2,401 chicken serum samples by the enzyme-linked immunosorbent assay (ELISA). The results of monitoring tests of samples received from 31 poultry farms (nine RF Subjects) indicate a decrease in the number of Mycoplasma gallisepticuminfected stocks and stable Mycoplasma synoviae situation. The respiratory mycoplasmosis epidemic situation on indoor poultry farms might have improved due to obtaining the poultry for commercial parent stocks from mycoplasmosis-free sources, better sanitary and hygienic conditions, elimination of the disease provoking factors, and the use of the disease-specific means of prevention in the parent broiler stocks. The infectious synovitis situation remains tense despite the fact that the number of Мycoplasma synoviae-infected farms decreased in comparison with the monitoring results for 2015–2018. Most seropositive stocks were detected on the layer farms (50.0% – in 2019). It seems appropriate to increase the amount of tests to be performed and the number of farms covered by testing in 2020 to more fully present the disease spread situation in commercial poultry farming in Russia.